Al-Tansiq fi Taklim al-Lughah al-'Arabiyyah - Mohammad Zainal Hamdy (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2019)
The teacher is the leader of the teaching and learning process and has a significant influence on shaping learners’ behavior. Therefore, a teacher does not merely teach and deliver lessons, but also educates, guides, and supervises learners throughout the entire learning process. In order to carry out his or her duties and responsibilities, an Arabic language teacher must possess excellent linguistic competence and also have a deep understanding of various disciplines, so as to be able to influence learners cognitively, affectively, and behaviorally. Thus, the school must determine clear and well-planned objectives to facilitate all members in measuring and achieving these goals. Consequently, the development of planning and organization, whether in teaching or curriculum design, is a necessary requirement. In addition, the school should strengthen its role in enhancing the professional competence of other teachers. Coordination is known to play a central role, namely in developing the integration of teaching staff, improving their abilities and performance, developing the curriculum, and conducting research to improve the teaching process.